2017
DOI: 10.1038/onc.2016.515
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages confer survival signals via CCR1-dependent translational MCL-1 induction in chronic lymphocytic leukemia

Abstract: Protective interactions with bystander cells in micro-environmental niches, such as lymph nodes (LNs), contribute to survival and therapy resistance of chronic lymphocytic leukemia (CLL) cells. This is caused by a shift in expression of B-cell lymphoma 2 (BCL-2) family members. Pro-survival proteins B-cell lymphoma-extra large (BCL-XL), BCL-2-related protein A1 (BFL-1) and myeloid leukemia cell differentiation protein 1 (MCL-1) are upregulated by LN-residing T cells through CD40L interaction, presumably via nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…In the first place, we focused on the cell-autonomous response of the CLL cells towards BIRD-2. However, interactions with bystander cells in micro-environmental niches support CLL cells by providing survival and proliferative signals [37][38][39]. Hence, these unsupported experiments were restricted towards short-term BIRD-2 application to limit spontaneous cell death, correlating with loss of Bcl-2-family members such as Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first place, we focused on the cell-autonomous response of the CLL cells towards BIRD-2. However, interactions with bystander cells in micro-environmental niches support CLL cells by providing survival and proliferative signals [37][38][39]. Hence, these unsupported experiments were restricted towards short-term BIRD-2 application to limit spontaneous cell death, correlating with loss of Bcl-2-family members such as Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In the dot plots, each CLL sample is represented with a different color, which is shown in the titles of the individual bar graphs. Statistically significant differences were determined using a one-tailed paired t-test (**P < 0.01) anti-apoptotic Mcl-1 due to rapid loss of supportive signals [37]. Therefore, we also performed experiments in CLL cells supported by CD40L-expressing fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These pro-survival signals result in a nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB)-dependent upregulation of B-cell lymphoma 2 (BCL2) family members BCL2-related protein A1 (BFL-1) and B-cell lymphoma-extra large (BCL-X L ), 20 and protein kinase B (AKT)-dependent upregulation of induced myeloid leukemia cell differentiation protein (MCL-1). 21 With respect to CLL proliferation, mitogen-activated protein kinase (MAPK) and signal transducer and activator of transcription (STAT)3 pathways play additional roles. 22…”
Section: Introductionmentioning
confidence: 99%
“… 56 We recently found that MDC-mediated survival depended on chemokine signaling via CCR1. 21 Nurse-like cells are monocyte-derived cells which develop following prolonged in vitro culture with CLL cells 55 and have been identified in both the spleen and lymph nodes of CLL patients. 57 Nurse-like cells are thought to induce CLL survival effects via factors such as A proliferation inducing ligand (APRIL), B-cell activating factor (BAFF) or C-X-C motif chemokine (CXCL)12 (reviewed by Ten Hacken & Burger 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A relatively new therapeutic target in CLL is colony-stimulating factor 1R (CSF1R), expressed on tumor-associated macrophages (TAMs), and macrophage killing by CSF1R blockade induces CLL cell death, primarily through the tumor necrosis factor pathway 128 . TAMs provide support to CLL cells via a PI3K-AKT-mammalian target of rapamycin (mTOR)-dependent translational upregulation of MCL-1 129 . Both small-molecule kinase inhibitors (for example, pexidartinib 130 and BLZ945 131 ) and monoclonal antibodies targeting CSF1R are in development for various tumor types.…”
Section: Emerging Drug Targetsmentioning
confidence: 99%